Love me forever - Lindsey, Johanna (W. Morrow, 1995)
In 19th Century Britain, Kimberley, an heiress searching for a husband to get away from her father, finds him in the person of Lachlan, rich and tall like her, but he loves another. When Lachlan is framed for the theft of a horse, Kimberley sees an opportunity to show him he can't do without her.